2009
DOI: 10.2220/biomedres.30.279
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simultaneous detection of 6 types of human herpes virus (herpes simplex virus, varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, human herpes virus 6A/B, and human herpes virus 7) by multiplex PCR assay

Abstract: A multiplex PCR assay was developed that enabled the simultaneous detection of DNA from 6 types of human herpes virus, HSV-1/2, VZV, EBV, CMV, HHV-6A/B, and HHV-7, using appropriate primer sets and conventional PCR techniques and instruments, with PCR products for each type of virus designed to be easily distinguishable by size. Electropherograms obtained from conventional agarose gels showed that, for each type, the observed number of base pairs corresponded to the intended product and that bands were easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…A number of studies have suggested that the central nervous system is the site of persistent HHV-6 infection [3,[6][7][8][9]. However, only 3 cases of ocular inflammation-associated HHV-6 have been reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested that the central nervous system is the site of persistent HHV-6 infection [3,[6][7][8][9]. However, only 3 cases of ocular inflammation-associated HHV-6 have been reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, DNA was extracted from specimens using a QIAamp DNA Blood Mini Kit (Qiagen, Valencia, CA, USA). Six primer sets were used in the multiplex PCR assay [6]. The PCR primers (sense and antisense, respectively) were 5 0 TGT TGG CCT TCA TGA CCC TTG TGA AA 3 0 and 5 0 TAG CTC GAG AGC TTG ATC TTG TCG GTT 3 0 for herpes The results of the multiplex PCR showed genomic DNA for HHV-6 but not for HSV types 1 and 2, VZV, EBV, or CMV (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Serology may sometimes be preferred rather than PCR [27]. However, the use of PCR in the present work is justifiable due to sensitivity of the test and the ability to amplify small amounts of the target sequence as showed in previous studies [29,32,[39][40][41][42][43][44][45][46]. In our study, precautions against PCR contamination were taken.…”
Section: Discussionmentioning
confidence: 96%
“…developed a multiplex-PCR assay for rapid and simultaneous detection of six types of human herpes viruses, including HSV and VZV. In that study, the PCR assay had a lower detection limit of approximately 20 viral copies per reaction (0.8 copies/µL) for each type of virus 15 . In this regard, there is a small variation of sensitivity in different studies, which can be explained by several factors, such as the sequence of primers chosen, enzyme activity, DNA extraction method and the detection method used.…”
mentioning
confidence: 90%
“…In addition, for reactions with dilutions between 2.5 and 12 copies, 50% were positive by RT-PCR, and 12.5% were positive by nested-PCR 14 . Furthermore, Tanaka et al 15 . developed a multiplex-PCR assay for rapid and simultaneous detection of six types of human herpes viruses, including HSV and VZV.…”
mentioning
confidence: 99%